A comparative study for the agricultural tractor selection problem - Ayşegül Tuş Işık; Esra Aytaç Adalı (Decision Science Letters, 2016)
Agricultural tractor selection is vital for farms, farmers or other agricultural companies in terms of success and competitiveness in the global market. This selection may be assumed as a MCDM (Multi Criteria Decision Making) problem involving qualitative and quantitative factors that must be simultaneously integrated into the selection process. At the same time there are many agricultural tractor alternatives in the market when purchasing an agricultural tractor. This paper deals with the agricultural tractor selection problem using TOPSIS method. This problem is also solved with two other MCDM methods; COPRAS (COmplex PRoportional ASsessment) and EVAMIX (EVAluation of MIXed Data) to rank the tractors alternatives. Lastly Borda and Copeland methods are used to aggregate all three ranking results.